Adorno and art as mediation of utopia - Maya Franco, Claudia María (Estudios de Filosofía, 2004)
Adomo's Aesthetic Theory is one of the most accomplished attempts to take modern art to its concept. Its starting point is the recognition of the social nature of the aesthetic fact as well as the resistance of modem an with respect to any kind of social goal. This double nature has social fact and autonomy constitutes art as a critical element within the social so the endeavor of conceptualisation takees on social criticism. The nature of aesthetic criticism makes art mediate between the social and utopia.